Strategic planning using combinatorial game theory on chess endgames - Jimenez, Carlo Miguel Co (Animo Repository, 2022)
Chess is a classic board game that most people know about. Much research regarding chess has already been done, including the optimal opening strategies a player can do, the million possible combinations of a single chess game, possible endgame situations, and many more. This study is an exposition of the paper on chess endgames written by Zvi Retchkiman Königsberg. In this paper, we analyze and discuss strategies for chess games formed only by pawns and built around a position called Zugzwang. In such a position, a player is forced to be in a situation where it would be more beneficial to skip a turn than make a move. To help the reader better understand the concepts tackled in the paper, basic concepts of combinatorial game theory are discussed with illustrations specifically constructed in chess game scenarios. It is the goal of this thesis to provide easy-to-read material that will be useful for those who would like to study combinatorial games as applied to the game of chess.